Prognostic factors in ALS: a comparison between Germany and China - Dorst, Johannes; Chen, Lu; Rosenbohm, Angela; Dreyhaupt, Jens; Hübers, Annemarie; Schuster, Joachim; Weishaupt, Jochen H.; Kassubek, Jan Rainer; Gess, Burkhard; Meyer, Thomas; Weyen, Ute; Hermann, Andreas; et al. (Journal of neurology, 2019)
Amyotrophic lateral sclerosis, motor neuron disease, prognostic factors, survival, Germany, China